Individual differences in feelings of certainty surrounding mixed emotions - Anthony G. Vaccaro; Shruti Shakthivel; Helen Wu; Rishab Iyer; Jonas Kaplan (PLoS ONE, 2025)
Ambivalence and uncertainty, though related, are distinct constructs. While research has explored the link between certainty judgements and ambivalence in the context of attitudes and beliefs, little is known about individual differences in how certain people feel about identifying their own ambivalent, or mixed, emotions in the moment. In two samples, we investigated the relationship between the intensity of mixed emotions and self-reported certainty of one’s own current affective experience on a trial-to-trial basis. We additionally tested whether this relationship was moderated by personality and emotional traits. First, in a sample of 140 participants, we found a significant negative relationship between the intensity of mixed feelings and affective certainty, and this relationship was weaker in those with higher emotional intelligence. We next conducted a pre-registered online study with 311 participants in a sample more demographically representative of the United States. We replicated our finding that uncertainty was predicted by higher intensity of co-occurring positive and negative affect, but did not replicate the moderating effect of emotional intelligence. Trait meta-mood, however, did moderate this relationship. Our results show that despite the abstract nature of asking people to report how certain they are of how they feel, and potentially differing interpretations of the question, meaningful variation is found in responses. Future work can refine methods of gauging affective uncertainty, and the implication of affective certainty for mixed emotions on well-being.